Strengthening postgraduate programmes towards research excellence and industrial relevance foresight of biotechnology industry needs. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2009)

(untitled)
Globally, modern biotechnology is now a little over three decades old (Baltimore, 2008). Having gone past the infancy stage it is now in its maturing phase of striving to achieve its agenda for the millennium, namely to heal, feed, fuel and clean the world. In Malaysia, the industry lags behind achievements by the major global players (Ahmad Zaharudin, 2005).